A Census of the LyC Photons that Form the UV Background During Reionization - Katz, H; Kimm, T; Haehnelt, M; Sijacki, D; Rosdahl, J; Blaizot, J (Oxford University Press, 2018)
We present a new, on-the-fly photon flux and absorption tracer algorithm designed to directly measure the contribution of different source populations to the metagalactic ultraviolet (UV) background and to the ionization fraction of gas in the Universe. We use a suite of multifrequency radiation hydrodynamics simulations that are carefully calibrated to reproduce a realistic reionization history and galaxy properties at z ⩾ 6, to disentangle the contribution of photons emitted by different mass haloes and by stars with different metallicities and ages to the UV background during reionization. While at very early cosmic times low-mass, metal-poor haloes provide most of the Lyman continuum photons, their contribution decreases steadily with time. At z = 6 it is the photons emitted by massive systems ( Mhalo/M⊙>1010h−1 ) and by the metal enriched stars (10−3 < Z/Z⊙ < 10−1.5) that provide the largest contribution to the ionising UV background. We demonstrate that there are large variations in the escape fraction depending on the source, with the escape fraction being highest ( ∼45--60percent ) for photons emitted by the oldest stars that penetrate into the intergalactic medium via low opacity channels carved by the ionising photons and supernova from younger stars. Before H II regions begin to overlap, the photoionization rate strongly fluctuates between different, isolated H II bubbles, depending on the embedded ionising source, which we suggest may result in spatial variations in the properties of dwarf galaxies.